Atrial fibrillation in young patients. (3rd July 2018) - Gourraud, Jean-Baptiste; Khairy, Paul; Abadir, Sylvia; Tadros, Rafik; Cadrin-Tourigny, Julia; Macle, Laurent; Dyrda, Katia; Mondesert, Blandine; Dubuc, Marc; Guerra, Peter G.; Thibault, Bernard; Roy, Denis; et al.
ABSTRACT: Introduction : Atrial fibrillation (AF) is the most frequent arrhythmia worldwide. While mostly seen in elderly, it can also affect young adults (≤ 45 years of age), older adolescent, and children. Areas covered : The aim of this review is to provide an overview of the current management of AF in young patients. Specific issues arise over diagnostic workup as well as antiarrhythmic and anticoagulation therapies. The future management and diagnostic strategies are also discussed. Expert commentary : Management of AF in the young adult is largely extrapolated from adult studies and guidelines. In this population, AF could reveal a genetic pathology (e.g. Brugada, Long QT or Short QT syndromes) or be the initial presentation of a cardiomyopathy. Therefore, thorough workup in the young population to eliminate potential malignant pathology